Book Review: Language Curriculum Design (Monitoring, Assesment and Evaluation) - Sardi, Ahmed; Atmowardoyo, Haryanto (Celebes Journal of Language Studies, 2022)
The goal of a book review is to inform and assess the quality and content of a book. It offers reviews and critiques of the I. S. P. Nation and John Macalister work on language curriculum design. Chapters seven (7) of Monitoring and Assessment and chapter eight (8) of Evaluation were divided by the reviewer into two primary portions. To get things started, the monitoring and assessment chapter is informatively introduced in language and expanded upon in straightforward words similar to those found in every single subtopic. Second, chapter eight discusses evaluation, which provides professors and students with important and helpful information to enhance the course or to help them decide whether to keep the course or toss it. The critique of this part will include an assessment of the writer's visual style and content.